The Role of Parasocial Relationships in Minimizing the Affiliate Marketing Risks of the Generation Z - Fabilia, Safira; Aprianingsih, Atik (Universitas Mercu Buana, 2024)
Objectives: The objective of this study is to investigate whether the parasocial relationships can mitigate perceived risks in clicking affiliate marketing links. It also seeks to uncover strategies for affiliate marketers to boost click intention by understanding how these relationships reduce perceived risks.Methodology: This study employs a quantitative research method, utilizing surveys to gather data. It involved 384 Indonesian Gen Z respondents who are not only knowledgeable about affiliate marketing but also have at least one favorite marketer. The collected data was analyzed using Structural Equation Modeling (SEM) with the software SmartPLS 3.2.9.Finding: The research uncovers that liking and perceived similarity have a positive effect on parasocial relationships. Furthermore, the parasocial relationship has a positive effect on risk reduction, which, in turn, positively affects the intention to click.Conclusion: The study concludes that successful affiliate marketers can benefit from harnessing parasocial relationships. This research offers practical insights for affiliate marketers seeking to increase their effectiveness and consumer engagement, highlighting the unique opportunity to boost click-through rates through the strategic use of parasocial relationships.